Metais pesados em áreas agrícolas e Cerrado nativo no Oeste da Bahia - Santos, Douglas da Silva (2019)
All and any activity has the potential to add to the environment heavy metals with the potential to cause contamination of soil, water and air damaging and often irreversible . The process of food production requires the use of inputs for the control pests and diseases and others capable of altering the chemically and physically properties of the soil to ensure high yields. However, the intensive and continued use to such inputs can add heavy metals to the soil. To ensure that activities such as the process of producing food is safe, and minimize any risk to the health of people, animals and the preservation of the environment. For that to happen, in addition to the use of inputs free of toxic elements assessments of the levels of soil must be carried out in order to verify potential risks. Therefore, the aim of this work is to evaluate the risk of contamination by heavy metals in western Bahia, determining the levels of Ba, Cd, Co, Cr, Cu, Ni, Zn, Mn, Al and Fe in agricultural áreas and in the native Cerrado . For this purpose, 10 áreas were selected in the West of Bahia: A1= Anel da Soja, A2 = Placas; A3= Bela Vista; A4 Novo Paraná; A5 = Panambi, A6= Coaceral; A7 = Alto Horizonte; A8 = Roda Velha; A9 =Roda velha de baixo e A10 = Cascudeiro. In each área, 8 properties were selected. Soil samples were collected in each soil at two depths (0-10 cm and 10-20 cm) in the following soil preparation systems: conventional tillage system (CT); no tillage (NT) and native Cerrado (NC). Aqua regia was used for extraction of the metals, and the extracts were dosed in ICP-Plasma. For the univariate procedures, we used descriptive statistics, Tukey test variance analysis, and the Student t test. The correlations between the variables were determined by calculating Pearson correlation coefficient. For the multivariate procedures, the principal component analyzes (PCA) were used.The results showed that the áreas A5 (Panambi) and A6 (Coaceral) presented higher levels of heavy metals in relation to the others áreas. The values of heavy metals found in the western region of Bahia are lower than the reference values of quality of other states. The soil preparation systems CT and NT presented higher levels than the NC áreas. The increasing order of heavy metals found in the CN was: Cd> Co> N i> Ba> Zn> Cr> Mn > Fe> Al.